2000
DOI: 10.1074/jbc.275.16.12200
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Activation of ERK Contributes to Glutamate-induced Oxidative Toxicity in a Neuronal Cell Line and Primary Cortical Neuron Cultures

Abstract: Oxidative stress can trigger neuronal cell death and has been implicated in several chronic neurological diseases and in acute neurological injury. Oxidative toxicity can be induced by glutamate treatment in cells that lack ionotrophic glutamate receptors, such as the immortalized HT22 hippocampal cell line and immature primary cortical neurons. Previously, we found that neuroprotective effects of geldanamycin, a benzoquinone ansamycin, in HT22 cells were associated with a down-regulation of c-Raf-1, an upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
404
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(438 citation statements)
references
References 67 publications
31
404
1
2
Order By: Relevance
“…On the other hand, it also has a role in apoptosis, which depends on cell type and on the signal that triggers cell death. It was observed that persistent activation of ERK 1/2 contributes to apoptosis in primary cortical neuronal cultures (Satoh et al, 2000;Stanciu et al, 2000). The SAPK/JNK is a central mediator of stress and is essential for the regulation of physiological and pathological processes (Johnson and Nakamura, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it also has a role in apoptosis, which depends on cell type and on the signal that triggers cell death. It was observed that persistent activation of ERK 1/2 contributes to apoptosis in primary cortical neuronal cultures (Satoh et al, 2000;Stanciu et al, 2000). The SAPK/JNK is a central mediator of stress and is essential for the regulation of physiological and pathological processes (Johnson and Nakamura, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, oxidative stress has been shown to activate ERK as a protective mechanism (Guyton et al, 1996;Aikawa et al, 1997;Bhatt et al, 2002). However, a proapoptotic role has been demonstrated for ERK in several studies with different stimuli, including anticancer drugs (Stanciu et al, 2000;Wang et al, 2000;Guise et al, 2001;Xiao and Singh, 2002;Lee et al, 2003;Zhang et al, 2003;Nguyen et al, 2004).…”
Section: Hpr-induced Apoptosis In Hnscc Cellsmentioning
confidence: 99%
“…The molecular mechanisms underlying oxidative stress-induced neuronal damage are emerging and appear to involve an apoptotic mode of death in which ERK1/2 [175,196] and JNK [48,136,226] have been strongly implicated. Furthermore, there is strong evidence for involvement of mitochondrial defects in neurodegenerative diseases, with neuronal cell death arising directly from mitochondrially generated ROS, ATP depletion or activation of the mitochondrialdependent apoptotic pathways [48,202,226].…”
Section: Apoptosis Mitochondrial Function and Mapk Signal Transductionmentioning
confidence: 99%